IJFANS INTERNATIONAL JOURNAL OF FOOD AND NUTRITIONAL SCIENCES ISSN PRINT 2319 1775 Online 2320 7876 Research paper © 2012 IJFANS. All Rights Reserved, UGC CARE Listed ( Group -I) Journal Volume 11, Iss 10, 2022 (International Journal of Food and Nutritional Sciences, 2022)
A simple preparative procedure was adopted for Extraction and Partial purification of Invertase enzyme from White edible mushroom (Agaricus bisporus). A homogenised extract of the mushroom was first saturated by Ammonium sulphate (30% - 80%) and followed by the partial purification by Dialysis method. The partially purified mushroom samples were subjected to Lowry‟s method for Protein Estimation and Enzyme Activity. The apparent Vmax and Km values were determined for different concentrations of sucrose as substrate respectively. The Maximum activity of Invertase from the partially purified Mushroom sample at optimum temperature and pH were determined respectively. The kinetic properties of Invertase were determined by Michealis – Menten Kinetics and using the inverse Km and Vmax values, the double reciprocal, Lineweaver burk Kinetics was studied.